Biomimicry and Soils as a Subject of Law in a Society of Environmental Conflicts: a Fundamental Pillar in the Construction of Ecological Civilization in the 21st Century - Bernal Zamudio, Hernando (Revista Calarma, 2023)
Food production is multidimensional due to its influence on the international economy and, therefore, its impact on the human economy and the “economy of nature” so that any civilization can endure and progress over time current. By the preceding, humanity and its civilization are at the crossroads of producing quality, accessible and safe food since this is restricted by the destruction of the natural base, expressed by the concentration of land as private property and by the decrease in soil fertility in its organic, mineral, and biological phase (micro and macro fauna), which impacts water and hydrobiological resources, air quality and the dynamics of diverse forests in forest species. The legal framework must be developed so that soils are considered a law subject so that this and future generations can live in harmony with nature.